Effect of rapid solidification and calcium additions on Sn-38 wt.%Pb-6 wt.%Sb melt-spun alloys (JOURNAL OF ADVANCES IN PHYSICS, 2015)
The effect of calcium additions on the structure and physical properties of melt-spun process Sn-38Pb-6Sb alloys have been experimentally investigated at a solidification rate of ~105 K/s. Structure, internal friction, elastic moduli, microhardness and electrical resistivity of the Sn-38%Pb , Sn-38%Pb -6%Sb , Sn-38%Pb -6%Sb-0.5%Ca , Sn-38%Pb -6%Sb -1%Ca , Sn-38%Pb -6%Sb -1.5%Ca , Sn-38%Pb -6%Sb -2%Ca , Sn-38%Pb -6%Sb -2.5%Ca (in wt%) rapidly solidified alloys are investigated. The results showed that the mechanical and electrical properties values are enhanced for ternary Sn-38%Pb -6%Sb alloy. The examined mechanical and electrical conductivity decreased by addition of calcium content in the studied alloys. It also leads to with increasing Ca content the SnSb inter-metallic compound (IMC) precipitates are increased in the Sn matrix. The results were explained in terms of the dislocation theory, effect of quenching rate on the produced density fluctuations in composition and the modes of interaction of crystal lattice defects.